The effect and underlying mechanism of yeast β-glucan on antiviral resistance of zebrafish against spring viremia of carp virus infection - Liang, Hui; Li, Yu; Li, Ming; Zhou, Wei; Chen, Jie; Zhang, Zhen; Yang, Yalin; Ran, Chao; Zhou, Zhigang (Frontiers in Immunology, 2022)
β-glucan has been used as immunostimulant for fish. However, the effect of yeast β-glucan on viral infections has been less studied in fish. In this study, we investigated the effects of β-glucan on the resistance of zebrafish against spring viraemia of carp virus (SVCV) and elucidated the underlying mechanisms. Zebrafish were fed with a control diet or diet supplemented with 0.01% and 0.025% β-glucan for 2 weeks, and were challenged by SVCV. Zebrafish embryonic fibroblast (ZF4) cells were treated with 5 μg/mL β-glucan and were infected by SVCV. We further investigated the effect of β-glucan on autophagy level post SVCV infection. The intestinal microbiota was evaluated by 16S rRNA gene pyrosequencing. Results showed that dietary supplementation of 0.025% β-glucan significantly increased survival rate of zebrafish compared with control group after SVCV challenge (P < 0.05). Dietary β-glucan significantly increased the expression of genes related to type I IFN antiviral immune pathway in the spleen of zebrafish after viral infection, including type I IFN genes (ifnφ1, ifnφ2, ifnφ3), IFN-stimulated genes (mxb, mxc), as well as other genes involved in the IFN signaling pathway, including tlr7, rig-1, mavs, irf3 and irf7. Furthermore, β-glucan can inhibit the replication of SVCV in ZF4 cells. β-glucan did not stimulate type I IFN antiviral response in ZF4 cells, and the antiviral effect of β-glucan in ZF4 was independent of Myd88. Interestinly, β-glucan induced autophagy in ZF4 cells after SVCV infection. Inhibition of autophagy blocked the antiviral effect of β-glucan both in vitro and in zebrafish larvae model, suggesting that the mechanism of antiviral function of β-glucan involved autophagy induction. Lastly, dietary β-glucan changed the composition of intestinal microbiota in zebrafish, with reduced abundance of Proteobacteria and an enrichment of Fusobacteria and Firmicutes. To sum up, our results indicate that the β-glucan enhanced resistance of zebrafish against SVCV and stimulated type I IFN antiviral immne response of fish after viral infection. Furthermore, our results implicated the involvment of autophay induction in the antiviral mechanism of β-glucan.